Recurrent Cerebellar Desmoplastic/Nodular Medulloblastoma in Cerebrospinal Fluid (CSF) in the Elderly. A Cytologic Diagnosis - Kalogeraki Alexandra; Tamiolakis Dimitrios; Mavrigiannaki Panagiota; Karvelaskalogerakis Michael; Datseri Galateia; Agelaki Sophia; Papadopoulos Savvas (Sciendo, 2016)
Desmoplastic medulloblastoma is a rare subtype of medulloblastoma in childhood and more rare in adults. Cerebrospinal fluid (CSF) occurrence is frequent and important for treatment and prognosis. We report the CSF cytologic features of recurrent desmoplastic/nodular medulloblastoma in a 30-aged male.